Effect of different types of soil covers on sediment concentration and hydraulic parameters - Zuliziana Suif; Muhammad Izzul Akhtar; Nordila Ahmad; Maidiana Othman; Mohd Asri Md Nor (Penerbit Universiti Kebangsaan Malaysia, 2021)
Soil erosion issue is common among construction sites. The phenomena usually takes place on sloped areas with no soil cover. The main objectives of the research are to determine the sediment concentration of rain induced on different types of covers and also to determine the hydraulic parameters. Besides that, the research also has to investigate the relation of the sediment concentration with hydraulic parameters. This research will take place in rainfall simulator using soil sample collected from sloped areas. The hydraulic parameters of this experiment consist of flow velocity, flow depth, shear stress, and unit stream power. Soil sample will be placed on four trays with different types of covers and properly arranged in the rainfall simulator with slope of 20 ᵒ. The sample will undergo rainfall event for two hours. The surface runoff collected and the sediment concentration measured using Total Suspended Solid (TSS) testing. The result shows the stream power of dry leaves is higher among those four covers with 0.0046 msˉ¹ followed by grass cover with 0.0033 msˉ¹ than gravel with 0.0023 msˉ¹, and lastly bare soil cover with 0.0008 msˉ¹. However, sediment concentration and surface runoff that were produced by bare soil is the highest followed by gravel, then leaves, and lastly grass. Generally, the sediment production in descending order started with the bare soil, gravel, dry leaves, and grass. From the research shown, rain induced on vegetation cover can be used as a low-cost initiative to control the soil erosion on construction slope area.